2022
DOI: 10.1186/s12866-022-02713-9
|View full text |Cite
|
Sign up to set email alerts
|

An endophytic Schizophyllum commune possessing antioxidant activity exhibits genoprotective and organprotective effects in fresh water fish Channa punctatus exposed to bisphenol A

Abstract: Background Oxidative stress is responsible for the onset of several chronic and degenerative diseases. Exogenous supply of antioxidants is reported to neutralize the effects of oxidative stress. Several synthetic antioxidants suffer from various side effects which necessitates the exploration of antioxidant compounds from natural sources. Endophytic fungi residing in the plants are gaining the attention of researchers as a source of novel antioxidants. Majority of the research conducted so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the fungal basidiomycete Granulobasidium vellereum , a wood endophytic fungus, possesses antifungal activity against wood decay fungi owing to its variety of sesquiterpenes [44]. Moreover, the antioxidant properties of the endophytic fungus P. caribaeo quercicola align with those found in Phellinus merrillii reported by Chang et al [45] Another basidiomycete fungal endophyte, Schizophyllum commune is reported to have good antioxidant potential [46]. As such, additional research will be needed to extract the bioactive substances from the endophytic isolate of P. caribaeo‐quercicola and examine the activities of those compounds on the host and other plants especially crop plants as well as in the commercial industry.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fungal basidiomycete Granulobasidium vellereum , a wood endophytic fungus, possesses antifungal activity against wood decay fungi owing to its variety of sesquiterpenes [44]. Moreover, the antioxidant properties of the endophytic fungus P. caribaeo quercicola align with those found in Phellinus merrillii reported by Chang et al [45] Another basidiomycete fungal endophyte, Schizophyllum commune is reported to have good antioxidant potential [46]. As such, additional research will be needed to extract the bioactive substances from the endophytic isolate of P. caribaeo‐quercicola and examine the activities of those compounds on the host and other plants especially crop plants as well as in the commercial industry.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are unstable, reactive, partially reduced oxygen derivatives produced as byproduct of normal metabolic processes.They include hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2 · − ), singlet oxygen ( 1 O 2 ), and hydroxyl radical ( · OH), that act as secondary messengers in cell signaling, also required for various biological processes in both normal and cancer cells (Yang et al 2018 ). In response to oxidative stress, the human body has antioxidant mechanisms that play important role in neutralization of free radicals and detoxification of oxidative stress damage (Sharma et al 2022 ). A variety of plants and microbes have been reported to exhibit antioxidant activities (Djebbah et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%